INCLUSIVE EDUCATIONAL TECHNOLOGY FOR STUDENTS WITH DYSLEXIA IN A HYBRID READING PROGRAM: A CASE STUDY IN AN INDONESIAN PRIMARY SCHOOL - Saiful Fallah; Ahmed Al-Harthy; Fatima Al-Said; Khaled Al-Sharqi (Journal Neosantara Hybrid Learning, 2025)
Dyslexia is a common learning difficulty that affects many students worldwide, including those in Indonesia. Students with dyslexia face significant challenges in traditional educational settings, particularly in reading and language development. Inclusive educational technologies offer promising solutions to support these students, especially in hybrid learning environments where both digital and traditional methods are integrated. This study aims to explore the effectiveness of inclusive educational technology in a hybrid reading program for primary school students with dyslexia in Indonesia. The research employs a case study methodology, focusing on a group of dyslexic students at an Indonesian primary school. Data was collected through classroom observations, interviews with teachers, and pre- and post-assessments of reading skills. The results indicate that the use of educational technology, such as text-to-speech tools, phonics-based apps, and digital reading platforms, significantly improved students' reading abilities and engagement. The hybrid program allowed students to learn at their own pace, providing tailored support that traditional methods could not offer. The study concludes that inclusive educational technology is a valuable tool for supporting students with dyslexia, enhancing their reading skills, and promoting greater inclusion in the classroom. These findings contribute to the growing body of research on educational technology and inclusive practices in primary education.